2000
DOI: 10.3354/meps198139
|View full text |Cite
|
Sign up to set email alerts
|

Temporal scaling and relevance of bivalve nutrient excretion on a tidal flat of the Seto Inland Sea, Japan

Abstract: Using an indirect and integrated approach, we quantified the magnitude and temporal variabiiity of the contribution of macrozoobenthos to the upward flux of inorganic nitrogen and phosphorus on a sandy tidal flat of the Seto inland Sea, Japan. From Apnl1994 to April 1996, we conducted monthly field surveys on the abundance and faunal composition of the macrozoobenthic communities inhabiting the lower part of the intertidal zone. Subsequently, we carried out 24 h day/night laboratory experiments on the nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 60 publications
6
49
0
Order By: Relevance
“…Also, the infauna type plays an important role in regulating the balance between mineralization and nutrient release. Bivalves, which made up 93% of the infauna biomass at Virksund, excrete the NH produced by mineralization via ϩ 4 the siphons directly to the overlying water (Magni et al 2000). The benthic microalgae therefore did not have the for just a couple of months during summer completely changed both the nutrient and oxygen budgets of these shallow-water sites.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the infauna type plays an important role in regulating the balance between mineralization and nutrient release. Bivalves, which made up 93% of the infauna biomass at Virksund, excrete the NH produced by mineralization via ϩ 4 the siphons directly to the overlying water (Magni et al 2000). The benthic microalgae therefore did not have the for just a couple of months during summer completely changed both the nutrient and oxygen budgets of these shallow-water sites.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nutrient fluxes at the sediment-water interface can influence or regulate the nutrient composition of the water column, and benthos behave as either sinks or sources of inorganic nitrogen (N), phosphorus (P), and silicon (Nixon 1981). In some cases, nutrient remineralization mediated by macrozoobenthos (e.g., Magni et al 2000) and in the sediment can supply a large proportion of autotrophic nutrient demand (Middelburg and Soetaert 2005). However, despite the current understanding of nutrient dynamics in estuaries, the role of benthic suspension feeders dominating rocky bottom habitats in nutrient dynamics has received little attention.…”
mentioning
confidence: 99%
“…Bartoli et al (2001) showed a linear increase in the NH 4 -N flux to the water column with increasing biomass of the clam R. philippinarum. Magni et al (2000) reported that the nutrient mineralization rate of infaunal bivalves (R. philippinarum and M. senhousia) was between 16 and 82 times higher than the diffusive flux from the sediment of tidal flats. Therefore, in this study, mineralization by the clam seemed to be a major source of DIN in the water column in LTHS.…”
Section: Nutrient Sourcesmentioning
confidence: 99%
“…Asmus and Asmus (1991) also suggest that the filtration activity of the mussel Mytilus edulis reduces standing stocks of phytoplankton, and that nutrient mineralization sustains primary phytoplankton production. Nutrient mineralization by infaunal bivalve species has been studied in laboratory and mesocosm experiments (Doering et al, 1987), in situ benthic chambers, sediment core incubations (Cockcroft, 1990;Yamamuro and Koike, 1993;Bartoli et al, 2001), and by quantification of the total upward flux of nutrients from sediments and subsequent estimation of the relative contribution of animal excretion (Nakamura et al, 1988;Kiibus and Kautsky, 1996;Magni et al, 2000;Hiwatari et al, 2002;Kohata et al, 2003). These studies have shown that nutrient mineralization is an important source for water-column primary production, and this concept is incorporated in the ecological model for infaunal bivalve fisheries (e.g., Zaldívar et al, 2003;Spillman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%